2018
DOI: 10.1021/acsomega.8b02121
|View full text |Cite
|
Sign up to set email alerts
|

Dihydroquinoline Carbamate DQS1-02 as a Prodrug of a Potent Acetylcholinesterase Inhibitor for Alzheimer’s Disease Therapy: Multigram-Scale Synthesis, Mechanism Investigations, in Vitro Safety Pharmacology, and Preliminary in Vivo Toxicology Profile

Abstract: We previously characterized a set of potent pseudo-irreversible inhibitors of acetylcholinesterase (AChE) based on a redox prodrug strategy. Among the various synthesized prodrugs, compound 1, namely DQS1-02, displayed favorable physicochemical properties and was chosen to achieve the necessary prerequisite investigations prior to preclinical evaluation. Herein, we first report a practical multigram-scale nine-step synthesis of prodrug 1 with a good overall yield (18%) as well as a full investigation on the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The stability of the carbamate 18 in buffer or in presence of BuChE and its possible in vitro decarbamoylation were tested. We used in this aim a new analytical method described by Alix et al [39] and developed for compound 5 [31]. Owing to its high homology with the active-site sequence of the human BuChE and its commercial availability, butyrylcholinesterase form equine source eqBuChE is commonly used for in vitro assays and was chosen for this study.…”
Section: Buche-dependent Decarbamoylationmentioning
confidence: 99%
“…The stability of the carbamate 18 in buffer or in presence of BuChE and its possible in vitro decarbamoylation were tested. We used in this aim a new analytical method described by Alix et al [39] and developed for compound 5 [31]. Owing to its high homology with the active-site sequence of the human BuChE and its commercial availability, butyrylcholinesterase form equine source eqBuChE is commonly used for in vitro assays and was chosen for this study.…”
Section: Buche-dependent Decarbamoylationmentioning
confidence: 99%
“…The in vitro decarbamoylation of 20 in the presence of AChE was established according to a new analytical method developed by Alix et al [19]. A large excess of Electrophorus electricus ( eel )AChE was added to a solution of 20 in a phosphate-buffered saline (PBS) buffer (pH 7.4) at 25 °C.…”
Section: Resultsmentioning
confidence: 99%
“…As a complement to the preceding studies, the ability of compounds 14 and 4 to cross the blood brain barrier (BBB) by passive diffusion was determined by PAMPA BBB assays. Unsurprisingly [39,40,41,42], the obtained values showed that the quinolinium salt 14 is not able to cross the BBB by this transport process (Pe = 0.00 × 10 −6 cm·s −1 ), whereas the dihydroquinoline compound 4 , which is more lipophilic, diffuses moderately (Pe = 2.41 × 10 −6 cm·s −1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Other reports also suggest a role of the DYRK1A activity in the amyloid beta peptide (Aβ) accumulation [34,35]. For many years, our group has been interested in the development of new ChEIs, with the aim of replacing the marketed AChEIs by more specific and less toxic ones [36,37,38,39,40,41,42]. In this context, we previously patented and reported on the design of brain-penetrant bio-oxidative prodrugs of potent pseudo-irreversible AChE carbamate-based inhibitors (Scheme 1A) [41].…”
Section: Introductionmentioning
confidence: 99%